Effectiveness Health Education Use Speech And Disccusion Methods Concerning On Narcotic Danger For Students Of 9th Class In Smp N I Banyudono - Ari Kustati; Atik Aryani; Wahyu Bintoro (Universitas Sahid Surakarta, 2017)
Background :There is 4 million people (2.18%) of Indonesian are narcotic user population 10-59 years old, from 4 million there are 1.6 million are trial stage, 1.4interview with teacher of SMP N I Banyudono, at this school was given narcotic counseling for from 10 students of 9th class, 5 students are have good knowledge about narcotic and the denger, 3 students know enough and 2 others was less. Purpose : To know about effectiveness health education use speech and discussionmethods conserning on narcotic danger for students of 9th class in SMP N I Banyudono. Metods : This research used Quasy Experimental Design. The approached Method was pretest-postest design. The population of the research were students of 9 th Class SMP N I Banyudono which amount 217 students consisted of 7 class, sampling technique use simple random sampling with the sample of the 31 students. The analysis of data used paired T Test. Results : The result of statistic research, increased of mean value on speech methods with t sampling pair was 15.81%, group used disscusion methods increased 19.73%. The conclusion was effectiveness of increasing students knowledge used disscuion methods was larger than speech methods. Summary : Health education about the danger of narcotic must be continued and givenearly to prevent abuse of narcotic on teenagers